The Beliefs About and Attitudes toward the Teaching of Pronunciation: Future English Teachers’ Perspectives - Nodistya Septian Indrastana (UMBanjarmasin, 2018)
The application of Communicative Language Teaching (CLT) approach has been popular in the field of English Language Teaching (ELT). However, there are some pros and cons related to the teaching of pronunciation within the CLT approach. This study, therefore, was conducted in order to reveal the beliefs about and attitudes toward the teaching of pronunciation from the perspectives of future English teachers in State University of Malang. An opinionnaire was adapted to collect the data from 45 participants. The result of the small survey shows that future English teachers in State University of Malang have positive attitudes toward the teaching of pronunciation. A large percentage of them believe that pronunciation can be taught to all levels of learners and that non-native speaking teachers are also able to teach pronunciation.